The Toxicity Test on Larvae of Shrimp (Artemia salina L.) of Lindur Fruit Peel Extract (Bruguiera gymnorrhiza) and Identification of Its Bioactive Compounds - Ana Mardliyah; Undri Rastuti; Santi Nur Handayani (Stannum : Jurnal Sains dan Terapan Kimia, 2021)
Indonesia is the most mangrove-rich country, both in terms of area quantity and number of species. Mangrove plants have potential as a source of medicinal compounds. Bruguiera gymnorrhiza is a type of mangrove plant which is a source of medicinal plants from the Rhizoporaceae family. Ethanol extract of the stem bark of B. gymnorhiza has been known to have cytotoxic activity with an IC50 of 508.19 µg/mL against myeloma cancer cells (Rahmah, 2021). The aim of this study was to determine the toxicity of lindur fruit peel extract (B. gymnorrhiza) on Artemia salina Leach shrimp larvae. Lindur fruit peel extraction was carried out by maceration method using methanol solvent which was then fractionated with n-hexane and ethyl acetate as solvent. All extract fractions obtained were then tested for toxicity against shrimp larvae Artemia salina Leach by BSLT (Brine Shrimp Lethality Test) method. Extract fractions with the highest toxicity were identified for their bioactive compounds using UV-Visible and FT-IR spectrophotometers. The results of the toxicity test showed that the lindur fruit peel extract was toxic to A. salina L. and the most toxic fraction was the n-hexane fraction with an LC50 value of 34.109 ppm. The results of the analysis using UV-Visible and FT-IR spectrophotometers the active compound in the hexane fraction of lindur fruit extract (B. gymnorrhiza) contains terpenoid which has double bond conjugated that showed by the existence of an electronic transition of π →π* that was conjugated and there are clusters of -OH, C=O, C=C, aromatic, C-H and C-O groups.